Leaflet.js Essentials. - III, Paul Crickard (Community experience distilled., 2014)
Starting with how to create maps, you will learn about choosing your basemap and customizing it by adding various attributes such as zoom, start view, pop ups, and so on. Once you have gained experience of creating your own map with Leaflet, you will move on to combining Leaflet with GeoJSON and adding geometry objects and features to your maps. Moving ahead, you will proceed to create custom markers using images and discover various plugins such as the Cluster Marker plugin, the Bouncing Marker, and the Animated Marker to animate and move markers. You will then explore the latest ESRI features available on Leaflet and make use of its updated JavaScript library. Finally, you will understand how Leaflet enables you to use Node.js, C#, and Python alongside its own library to efficiently create maps.